Corrosion and protection. - Bardal, Einar, ....- (London : Springer, 2004)
Samenvatting:Corrosion and Prevention is an essential guide for mechanical, marine andcivil engineering students and also provides a valuable reference forpracticing engineers. Bardal combines a description of practicalcorrosion processes and problems with a theoretical explanation of thevarious types and forms of corrosion, with a central emphasis on theconnections between practical problems and basic scientific principles.This well thought-out introduction to corrosion science, with excellentexamples and useful tables, is also extremely well illustrated with 167diagrams and photographs. Readers with a limited background in chemistrycan also find it accessible.
Keywords: Corrosie; Corrosiebestrijding